TL 18129 - Surgical treatment of hallux valgus using the percutaneous chevron technique - Lemos Rodrigues, Fábio; Ribeiro Lara, Luiz Carlos; Grajales, Juan Antônio; Azevedo Torres Filho, Lucio Carlos (Scientific Journal of the Foot & Ankle, 2019)
Objective: To clinically and radiographically observe the outcomes of the surgical treatment of moderate and severe hallux valgus using percutaneous distal chevron osteotomy. Methods: A total of 35 feet (33 patients) with moderate and severe hallux valgus were evaluated using the Couhling classification from June 2016 to January 2018. The mean patient age was 53 years, and the mean postoperative follow-up time was 13 months. All patients who underwent chevron osteotomy were evaluated before and after surgery using the American Orthopedic Foot and Ankle Society (AOFAS) scale. We measured the hallux valgus angle (HVA), the intermetatarsal angle (IMA) and the distal metatarsal articular angle (DMAA) using radiographic studies. Results: The AOFAS score increased by a mean of 54 points. The HVA decreased by a mean of 19°, the IMA by 7° and the DMAA by 11°. The median decrease in the length of the first metatarsal bone was 0.35 cm. Conclusion: Chevron osteotomy using the percutaneous surgical technique made it possible to correct moderate and severe hallux valgus deformities, with excellent angular correction and a significant increase in the AOFAS score.